Helenismo y filohelenismo en la obra de Goethe. A 250 años del nacimiento del poeta - Castillo Didier, Miguel (Byzantion Nea Hellás, 2015)
On the occasion of Goethe’s 250th birth anniversary, Miguel Castillo Didier examines the presence of Hellenic elements in the poet’s works. He constantly found ideas, inspiration and narrative milestones in classical Greek texts, as well as in historical and mythological characters. The author mentions the plays Iphigeneia in Tauride, Proserpina, Prometheus, and the epic Achilles’ Poem.. The most extensive analysis is focused on Faust II, where a clear Hellenic influence can be found. About this work the poet said: "This play comprises three thousand years, from the fall of Troy to the fall of Mesolonghi". In effect, from Hellen as symbol of beauty to the hymn to Euforion - which is a hymn to Lord Byron and his sacrifice in Mesolonghi - the Greek presence is very intense. The author mentions other aspects of Goethe’s philohellenism: his devote love to Modern Greece, his translations of classic and postclassic works, his reconstruction of Sophocles’ and Euripides’ works and his translation of modern Greek popular ballads.